Pengaruh Stres Kerja dan Komitmen Organisasi Terhadap Turnover Intention Pada Karyawan Bagian Produksi PT Widaya Inti Plasma Sidoarjo - Dhuriatul Hanifa (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2018)
PT Widaya Inti Plasma is a manufacturing company that enganged in the manufacture of shoes and sandals There is problem founded about turnover intention. This study aims to know and explain the effect of job stress and organizational commitment either partially or simultaneously on production employees.This study is a quantitative study with 171 sample of PT Widaya Inti Plasma production employees, by using random sampling technique.The result of this study shows that (1) Job Stress partially has a significant effect on production employees turnover intention, which t hitung is 6.09> t tabel 1.65 and the significant value is 0,000. (2) Organizational Commitment partially has not significant effect on production employees turnover intention, which t hitung is 0.61> t tabel 1,65 and the significant value is 0,542. (3) Job Stress and Organizational Commitment simultaneously has an effect on production employees turnover intention, which F hitung is 21.33 > F tabel 3,05 and the significant value is 0,000.